1998
DOI: 10.1046/j.1432-1327.1998.2560045.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in myosin mRNA and protein expression in denervated rat soleus and tibialis anterior

Abstract: Denervation differs from other models of reduced neuromuscular activation due to the absence of a nerve-muscle connection and limited data exists regarding the effects of denervation on myosin heavy chain (MHC) expression. Thus, adult MHC expression (I, IIa, IIx, IIb) was studied in the rat soleus and tibialis anterior (TA) at the mRNA and protein levels 2, 4, 7, 10, 14, and 30 days following sciatic nerve transection. MHC protein content was quantified with SDS/PAGE and mRNA levels with the RNaseprotection as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
53
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 20 publications
9
53
1
Order By: Relevance
“…The fiber type transformation seen in rabbit muscles did not differ from that in rat muscles examined at an earlier stage of denervation (5,23,25,34,56,59). In one of those studies, coexpression of the different isoforms showed that the switch occurred within individual fibers and not by replacement with fibers of another type (34).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The fiber type transformation seen in rabbit muscles did not differ from that in rat muscles examined at an earlier stage of denervation (5,23,25,34,56,59). In one of those studies, coexpression of the different isoforms showed that the switch occurred within individual fibers and not by replacement with fibers of another type (34).…”
Section: Discussionmentioning
confidence: 61%
“…There is also some suggestion that during this final stage muscle fibers are replaced altogether by fibrous and adipose tissue. As a result of the changes during the first phase the muscle declines to 20 -30% of its original mass by 3-4 wk (5,8,25,44,52,60), and by 1-2 mo it develops only 25% of its original isometric tetanic tension (8,47). In the denervated rat EDL muscle, tetanic force is reported to decline even further over this period, to 1-3% of control values (1,14,30); at this stage mean fiber area is only 20 -30% of control (1,46), falling to 2.5% of control over subsequent months (1,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mechanically skinned fibers; myosin heavy chain isoforms; lineage; sarcoplasmic reticulum; Ca 2ϩ and Sr 2ϩ sensitivity; Long-Evans hooded rat MAMMALIAN SKELETAL MUSCLE fibers display a broad spectrum of structural and functional characteristics determined by the complement of homologous, but not identical, molecular structures involved in the excitation-contraction-relaxation cycle (33,34,41). Cross-innervation (4, 6), denervation (16,17,26,28,37), and chronic low-frequency stimulation (7,20,33,34) experiments have produced compelling evidence that the pattern of neural stimulation plays a crucial role in determining the functional and/or structural properties of skeletal muscle (38). However, neural control of fiber phenotype does not extend to the entire complement of cellular structures responsible for muscle fiber function, as demonstrated by crossinnervation studies.…”
mentioning
confidence: 99%
“…This implies that there exist layers of regulation of gene expression at the mRNA and the protein level that might act differently and independently (Leberer et al, 1986;Huey and Bodine, 1998). …”
Section: Denervation Modelsmentioning
confidence: 99%